COVID-19: Examining the Impact of the Global Pandemic on Violent Crime Rates in the Central Valley of California - Avila, Derek; Gao, Huan; Randol, Blake; Chintakrindi, Sriram (International Journal of Criminology and Sociology, 2023)
This study focuses on how a global pandemic like COVID-19 affects violent crimes in the city of Stockton, California. The violent crimes that we will be examining are homicide, robbery, rape, simple assault, and aggravated assault. We obtained crime data from the LexisNexis Community Crime Map and obtained COVID-19 data from the San Joaquin County Health Department regarding the city of Stockton. We developed the results of this research by using time-series plots and interrupted time-series analysis. Our results demonstrate that COVID-19 caused a statistically significant change in the slope for rape, robbery, and simple assault violent crimes. Finally, we discuss in our policy implications section that the Stockton Police Department should establish more community outreach programs that could help prevent these types of violent crimes.